Effect of laser pulse duration on properties of metal and metal carbide nanoparticles obtained by laser in liquid synthesis. (June 2021) - Curcio, M.; De Bonis, A.; Santagata, A.; Galasso, A.; Teghil, R.
Highlights: Transition Metals ablation in liquid by ns and fs lasers has been studied. NPs properties depend on the growth mechanisms active with ns and fs lasers. Using short lasers particles with larger crystalline domains have been obtained. Abstract: The control of the parameters that affect the physic-chemical properties of nanoparticles obtained by laser ablation in liquid is of relevant importance to select size and composition of materials suitable for applications such as catalysis and biomedical materials. We have focused our attention on the role of laser pulse lenght on the dimension, composition and crystallinity of laser synthesized particles. We observed that the ablation in water and organic solvents with short laser source allows to achieve particles with large crystalline domains, usually. Pd particles with a median diameter of 7 nm and 10 nm and crystalline domain of 28 nm and 45 nm were obtained by fs and ns ablation in water, respectively. Particles wrapped in carbon shells were observed by ns ablation of transition metals in organic liquid. The decomposed organic molecules absorbed on the growing particles can hinder their coalescence, therefore smaller particles were obtained by ns ablation with respect to particles obtained by fs ablation in the same experimental conditions. HR-TEM and XRD analysis allow to state that, MoC, TaC and WC1−x particles were obtained both by fs and ns metals ablation in toluene and ns ablation in acetone. By ultrashort laser ablation of Mo, Ta and W in acetone MoC, Ta4 C3 and WC1−x  + WOx particles were observed, respectively.